The Team Project Method In Managers Training; The Turkish Online Journal of Educational Technology (TOJET); Spec. iss. 1 (2015, July) : 15th International Educational Technology Conference - IETC 2015 - Leontyeva E. G. Elena Gennadievna (2015, 2015)
Title screen